The Oxford handbook of international law in armed conflict - Clapham, Andrew; Gaeta, Paola (Oxford, United Kingdom : Oxford University Press, 2015)
Which human rights violations or war crimes allegations result in exclusion from the refugee regime? What human rights protections apply to someone declared an unlawful combatant? Which human rights obligations apply to the actions of armed forces acting abroad? Over the past ten years the content and application of international law in armed conflict has changed dramatically. An authoritiative and comprehensive study of the role of international law in armed conflicts, this Oxford Handbook engages in a broad analysis of international humanitarian law, human rights law, refugee law, international criminal law, environmental law, and the law on the use of force. With an international group of expert contributors, this book has a global, multi-disciplinary perspective on the place of law in war.--
Part I. Introduction -- Part II. Sources -- Part III. Legal regimes -- Part IV. Key concepts for humanitarian law -- Part V. Key rights in times of armed conflict -- Part VI. Key issues in times of armed conflict -- Part VII. Accountability/liability for violations of the law in armed conflict.
Includes bibliographical references and index.
ARC PPDM
Keywords: War (International law); Neutrality; Human rights